1997
DOI: 10.1136/jcp.50.7.548
|View full text |Cite
|
Sign up to set email alerts
|

A survey of general practitioners' views on autopsy reports.

Abstract: (C Clin Pathol 1997;50:548-552)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Information regarding sudden unexpected deaths are often difficult to obtain, but may be of great value to clinicians and for the bereaved relatives. In one large questionnaire study, 90% of GPs found an attached autopsy report useful and agreed that autopsies revealed lesions not detected in life 7. A considerable proportion also found the cause of death surprising and a significant number felt the report would modify their future clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding sudden unexpected deaths are often difficult to obtain, but may be of great value to clinicians and for the bereaved relatives. In one large questionnaire study, 90% of GPs found an attached autopsy report useful and agreed that autopsies revealed lesions not detected in life 7. A considerable proportion also found the cause of death surprising and a significant number felt the report would modify their future clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…In 1978 Roberts 49 summarized 58 papers to attest the value and importance of autopsy, and, years later, laymen, 62 pathologists 61,63 medical students 13 and physicians 9 all agree on the benefits of autopsies. Autopsy remains a vital tool in gaining knowledge about diseases, 17,27,36 and is a teaching tool in education 17 as well as a contributing tool to quality monitoring. 8,75 General practitioners indicate that autopsy results do indeed modify their future clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…8,75 General practitioners indicate that autopsy results do indeed modify their future clinical practice. 36 For epidemiological purposes autopsy gives precise information about the causes of death and contributes to an accurate monitoring of disease prevalence. 57 In veterinary medicine, too, there are surveys stressing the relevance of postmortem examination as a crucial part of quality monitoring and education.…”
Section: Introductionmentioning
confidence: 99%
“…The nursing literature contains very little about the autopsy, and we could find no formal study of the views of nurses on the autopsy, even though there have been many studies of the views of other health professionals and trainees, members of ancillary professions and of relatives (Karunaratne & Benbow 1997). However, we were able to find two substantial review papers (Souder & Trojanowski 1992, Rushton 1995), both including conventional accounts of the benefits of autopsy; one was paired with a highly negative riposte (Stephany 1995), which amounts to an eloquent and emotive re‐statement of the curious but prevalent view (Brown 1984, Start et al .…”
Section: Introductionmentioning
confidence: 99%